Cambridge IGCSE® Biology coursebook : Third edition - Jones, Mary; Jones , Geoff (Cambridge : Cambridge University Press, 2002)
This edition of our successful series to support the Cambridge IGCSE Biology syllabus (0610) is fully updated for the revised syllabus for first examination from 2016. Written by an experienced teacher and examiner, Cambridge IGCSE Biology Coursebook with CD-ROM gives comprehensive and accessible coverage of the syllabus content. Suggestions for practical activities are included, designed to help develop the required experimental skills, with full guidance included on the CD-ROM. Study tips throughout the text, exam-style questions at the end of each chapter and a host of revision and practice material on the CD-ROM are designed to help students prepare for their examinations. Answers to the exam-style questions in the Coursebook are provided on the CD-ROM.